LEACHATE WATER MODELING USING GEOLISTRIK METHOD OF RESISTANCE TYPE OF CONFIGURATION OF WENNER-SCHLUMBERGER AT TPAS AMPANG KUALO DISTRICT SOLOK WEST SUMATERA - Ridho Yovanda; Adree Octova; Yoszi Mingsi Anaperta (Departemen Teknik Pertambangan FT UNP, 2018)
TPAS Ampang Kualo is the final dumping place in Solok city of West Sumatra which is located near the residential area. Garbage accumulation in TPAS Ampang Kualo resulted in environmental pollution, therefore it is necessary to conduct research on TPAS Ampang Kualo with the aim to know the distribution of its waste. Estimation of the distribution of waste below the surface of the soil can be done by using the geolistrik type resistance method. Data retrieval with MAE X612 EM Resistivity meter using geoelectric method of resistance of configuration type Wenner - Schlumberger. The measurement data is then inverted using Res2dinv software to bring up the 2D resistivity profile and the Voxler 4.0 software for 3D resistivity profiles. The results showed that the leachate water of TPAS Ampang Kualo was almost evenly distributed. On Track one is around a leachate pond stretching from South to North, Lindi is detected from a range of 5 meters to 42 meters with a depth of 2.10 to 5.80 meters. On Track 2 also around a leachate pond stretching from East to West, Lindi is detected from a stretch of 7 meters to 44 meters with a depth of 1.50 to 6.35 meters. At Trajectory 3 is in the vicinity of a residential population stretching from South to North that cuts off the flow of leachate ditches, Lindi is detected from a 1 meter to 31 meter stretch with depths of 0.25 to 7.38 meters.Based on the results of the research and geological map in the area, point to the research area at TPAS Ampang Kualo subsurface layer composed of rocks and minerals, ie, clay, sand, gravel, and quartzite igneous rock.It was concluded that the distribution of waste at the TPAS Ampang Kualo to the south to the southwest followed the small flow of leachate discharge, due to the lower topography of the TPAS and the distribution of its waste also to the vicinity of Green Hills Arya housing.